2013
DOI: 10.1016/j.febslet.2013.01.008
|View full text |Cite
|
Sign up to set email alerts
|

The secreted oligomeric form of α‐synuclein affects multiple steps of membrane trafficking

Abstract: a b s t r a c t a-Synuclein (a-syn) can be secreted from neurons into the extracellular space, affecting the homeostasis of neighboring cells, but the pathophysiology of secreted a-syn remains largely unknown. We found that when exogenously applied to COS-7 cells, a-syn secreted from differentiated SH-SY5Y cells was taken up by dynamin-dependent endocytosis. Upon internalization, a-syn significantly increased the rate of transferrin receptor (TfR) internalization and recycling, and subsequently the surface lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 32 publications
(45 reference statements)
1
19
0
1
Order By: Relevance
“…However, severe loss-of-function mutations are likely to be lethal before birth (3) and have not been described in humans. Interestingly, SNCA and DNAJC13, mutated in patients with PD, modulate TFR1 trafficking (72)(73)(74). VPS35, another PD disease gene, helps sort TFR1 to recycling endosomes, and insufficiency of its retromer complex causes cellular iron deficiency (75).…”
Section: Resultsmentioning
confidence: 99%
“…However, severe loss-of-function mutations are likely to be lethal before birth (3) and have not been described in humans. Interestingly, SNCA and DNAJC13, mutated in patients with PD, modulate TFR1 trafficking (72)(73)(74). VPS35, another PD disease gene, helps sort TFR1 to recycling endosomes, and insufficiency of its retromer complex causes cellular iron deficiency (75).…”
Section: Resultsmentioning
confidence: 99%
“…This lack of consensus may indicate a non-specific nature of αSyn-induced microgliosis, or perhaps the capacity for multiple receptors to sense changes in the levels of extracellular αSyn, regardless of conformation. Investigations into the oligomeric secreted forms of αSyn are gaining momentum (Angot et al, 2012; Chai et al, 2013; Prots et al, 2013), but questions remain as to which αSyn specie is the most pathologically relevant. The recent use of neuronally secreted αSyn in this context may be particularly informative (Kim et al, 2013).…”
Section: Does α-Synuclein Represent a Pathologically Relevant Stimulamentioning
confidence: 99%
“…Lewy bodies and Lewy neurites, the neuropathological hallmarks of Parkinson disease and several neurological diseases, are mainly constituted by intracellular filamentous aggregates of the protein ␣-synuclein (␣-SN) 4 (1). In addition, recent studies have demonstrated the presence of misfolded or aggregated extracellular ␣-SN, suggesting that the pathogenic action of this protein might involve the transfer of ␣-SN from one cell to another through the extracellular space, with deadly consequences to the recipient cell (2)(3)(4)(5)(6). In vitro studies revealed that ␣-SN amyloid aggregation is a nucleation-dependent event that occurs in a process ranging from monomer via oligomers to fibrils (7,8).…”
mentioning
confidence: 99%